Rapid Identification and Evaluation of Neoantigen-reactive T-Cell Receptors From Single Cells. Issue 1 (January 2021) - Paria, Biman C.; Levin, Noam; Lowery, Frank J.; Pasetto, Anna; Deniger, Drew C.; Parkhurst, Maria R.; Yossef, Rami; Kim, Sanghyun P.; Florentin, Maria; Ngo, Lien T.; Ray, Satyajit; Krishna, Sri; et al.
Abstract : Engineered T cells expressing tumor-specific T-cell receptors (TCRs) are emerging as a mode of personalized cancer immunotherapy that requires identification of TCRs against the products of known driver mutations and novel mutations in a timely fashion. We present a nonviral and non–next-generation sequencing platform for rapid, and efficient neoantigen-specific TCR identification and evaluation that does not require the use of recombinant cloning techniques. The platform includes an innovative method of TCRα detection using Sanger sequencing, TCR pairings and the use of TCRα/β gene fragments for putative TCR evaluation. Using patients' samples, we validated and compared our new methods head-to-head with conventional approaches used for TCR discovery. Development of a unique demultiplexing method for identification of TCRα, adaptation of synthetic TCRs for gene transfer, and a reliable reporter system significantly shortens TCR discovery time over conventional methods and increases throughput to facilitate testing prospective personalized TCRs for adoptive cell therapy. Abstract : Supplemental Digital Content is available in the text.